Educação Ambiental, formação docente, mídias e tecnologias digitais: uma análise da produção divulgada em periódicos acadêmicos da área de educação (2023/2024) - Sousa, Viviane de (2024)
The present research aimed to analyze the production published in Environmental Education journals in the Brazilian Education area evaluated by Qualis Periodicals of CAPES in order to examine how these productions address the challenges and perspectives in relation to the integration of digital technologies in teacher training. The methodology used was an integrative literature review, which consists of a research method that aims to synthesize and integrate the results of studies on a specific topic, providing a broader and more complete understanding of the state of knowledge. 29 documents available on the Periodical Portal of the Coordination for the Improvement of Higher Education Personnel (CAPES) were analyzed, between the years January 2023 and November 2024. The articles were organized into four categories: a) Environmental Education and teacher training; b) Teachers’ conceptions of Environmental Education; c) Methodologies for the development of Environmental Education; d) Environmental Education, Technologies and media. The research revealed a wide diversity of approaches and investigations on the application of Environmental Education (EE). However, although there is a variety of perspectives and approaches to teacher training on concepts of Environmental Education, the number of publications related to the integration of digital technologies in teacher training in EA is relatively small when compared to the survey of publications in the aforementioned years, highlighting, thus, the need for theoretical and practical deepening in this field. It was realized that there is still a lot to evolve with regard to the inclusion of EA in teacher training courses and the exploration of pedagogical strategies and the use of digital technologies, in order to enable teachers to position themselves as actors in transforming their pedagogical practice.